2018
DOI: 10.1002/adma.201801362
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Blood–Brain Barrier: The Role of Nanomaterials in Treating Neurological Diseases

Abstract: Therapies directed toward the central nervous system remain difficult to translate into improved clinical outcomes. This is largely due to the blood-brain barrier (BBB), arguably the most tightly regulated interface in the human body, which routinely excludes most therapeutics. Advances in the engineering of nanomaterials and their application in biomedicine (i.e., nanomedicine) are enabling new strategies that have the potential to help improve our understanding and treatment of neurological diseases. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
393
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(400 citation statements)
references
References 560 publications
(972 reference statements)
1
393
0
6
Order By: Relevance
“…[ 2 ] BBB is mainly composed of brain endothelial cells, highly specialized basal membrane, pericytes embedded in the basal membrane, and astrocytic end feet. [ 3 ] The tight junction of complexes between adjacent endothelial cells further strengthens the functional integrity of BBB, which strictly monitors and controls the import and export of different substances of the brain. [ 4 ] It is reported that nearly 98% of small‐molecule drugs or contrast agents and most macromolecular drugs are routinely excluded from the brain, which makes the treatment and imaging of brain tumors extremely difficult.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] BBB is mainly composed of brain endothelial cells, highly specialized basal membrane, pericytes embedded in the basal membrane, and astrocytic end feet. [ 3 ] The tight junction of complexes between adjacent endothelial cells further strengthens the functional integrity of BBB, which strictly monitors and controls the import and export of different substances of the brain. [ 4 ] It is reported that nearly 98% of small‐molecule drugs or contrast agents and most macromolecular drugs are routinely excluded from the brain, which makes the treatment and imaging of brain tumors extremely difficult.…”
Section: Introductionmentioning
confidence: 99%
“…We achieved this by combined modulation of surface coating chemistry and coating density on nanoparticles, which maximized their active transport through BBB. Incorporating certain surface coatings on NPs has been previously shown to augment their active penetration across BBB in multiple brain diseases (21)(22)(23)(24). However, a surface coating that can facilitate active transport of siRNA NPs across BBB in TBI has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…The barrier elements in the central nervous system (CNS) are the blood‐brain barrier (BBB) formed by endothelial cells of capillaries, the cerebrospinal fluid (CSF) barrier formed by choroid plexus epithelial cells, and the meningeal barrier formed by arachnoid epithelial cells . The BBB is constituted by brain‐specific endothelial cells that differ from those in the microvasculature of the rest of the body by their absence of fenestrations, the tightness of their intercellular junctions, a relative lack of pinocytotic activity and, as recently demonstrated, by their unique lipid composition that precludes formation of caveolae and caveolar‐mediated transcytosis, governed by the transmembrane protein Mfsd2a . In addition to endothelial cells, the BBB includes the capillary basement membrane, a sheath of astrocytic foot projections and numerous pericytes embedded in it (Figure A).…”
Section: The Blood‐brain Barriermentioning
confidence: 99%
“…Tight junctions and adherens junctions act cooperatively, especially through ZO‐1 and catenins, thereby improving tight junction assembly and consequently curbing significantly the paracellular diffusion of polar solutes . The endothelial cells monolayer of the BBB is the tightest endothelial barrier in the body, with a trans‐endothelial electrical resistance (TEER) of 1500‐2000 Ω cm 2 . This brings up the first key question of this review, how do nutrients, hormones and other molecules traverse the BBB to reach the brain?…”
Section: The Blood‐brain Barriermentioning
confidence: 99%
See 1 more Smart Citation